FORMATION AND FUNCTIONING OF THE WORLD ENERGY MARKET: ECONOMIC PERSPECTIVES (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article examines the development of the world energy sector. It identifies new trends that are determined by the growth of integration processes, intensification of inter-fuel competition in the energy market, progress in the application of advanced technologies, production of new energy resources, the emergence of routes formed to establish a more successful mechanism for their transportation, and increased energy awareness. The article also notes that current trends are aimed at making electricity not only economically affordable but also environmentally friendly. A significant increase in electricity production in 2023 was observed, which led to an increase in carbon dioxide emissions both in the global electricity sector and in individual countries. Based on an analysis of the dynamics of global energy supply, the author identifies an increase in renewable energy sources (wind, solar, etc.) compared to previous years. It is shown that many countries, seeking to ensure energy security, make nuclear energy an important part of their energy strategies. Notwithstanding the fact that some countries are gradually abandoning nuclear power or decommissioning plants ahead of schedule, it is predicted that nuclear generation will grow by an average of almost 3% per year until 2026.The global energy market is influenced by a multitude of factors, both primary and secondary, which collectively aim to guarantee the stability and reliability of the energy supply system. These factors also serve to determine the extent to which a country can be considered to have achieved an adequate level of energy security. The energy sector in Ukraine, which is particularly vulnerable due to the introduction of martial law in the country since February 2022, is therefore susceptible to fluctuations in the global energy market.
Keywords: energy, energy supply, environmental pollution, renewable energy sources, nuclear energy